Multi-stage structure-based virtual screening approach combining 3D pharmacophore, docking and molecular dynamic simulation towards the identification of potential selective PARP-1 inhibitors - Mahmoud A. El Hassab; Wagdy M. Eldehna; Ghaneya S. Hassan; Sahar M. Abou-Seri (BMC Chemistry)
Abstract Presently, humanity is confronted with a range of diseases that have high death rates, especially those linked to cancerous growths. Several enzymes and proteins have been discovered as highly attractive targets for cancer treatment. The PARP family consists of 17 members and plays a crucial role in repairing DNA damage, which enables the survival of cancer cells. PARP-1 and, to a lesser extent, PARP-2 display above 90% activity in response to DNA damage, thereby distinguishing them apart from other members of the PARP family. Elevated levels of PARP-1 were observed in many types of tumor cells, such as breast, lung, ovarian, prostate, and melanomas. In an attempt to provide a future guide for developing selective inhibitors for PARP-1 over PARP-2 to minimize the resulting side effects from PARP-2 inhibitors, we constructed a structure-based virtual screening approach (SBVS). Firstly. A 3D pharmacophore was constructed based on the interaction of the selective inhibitor compound IV. After that, a database of nearly 450,000 phthalimide-containing inhibitors was screened through the validated pharmacophore, and 165 compounds were retrieved. The retrieved compounds were docked into the active site of PARP-1 where only 5 compounds MWGS-1-5 achieved a favorable docking score than the reference IV (-16.8 Kcal/mol). Redocking of the five compounds should have excellent selectivity for PARP-1 over PARP-2, especially compound MWGS-1. Further endorsement via molecular dynamics has proven higher affinity and selectivity for MWGS-1 towards PARP-1 over PARP-2, in which PARP-1- MWGS-1 and PARP-1- MWGS-1 achieved RMSD values of 1.42 and 2.8 Å, respectively.